Does the Heel’s Dissipative Energetic Behavior Affect Its Thermodynamic Responses During Walking? - Papachatzis, Nikolaos; Slivka, Dustin R.; Pipinos, Iraklis I.; Schmid, Kendra K.; Takahashi, Kota Z. (Frontiers in Bioengineering and Biotechnology, 2022)
Most of the terrestrial legged locomotion gaits, like human walking, necessitate energy dissipation upon ground collision. In humans, the heel mostly performs net-negative work during collisions, and it is currently unclear how it dissipates that energy. Based on the laws of thermodynamics, one possibility is that the net-negative collision work may be dissipated as heat. If supported, such a finding would inform the thermoregulation capacity of human feet, which may have implications for understanding foot complications and tissue damage. Here, we examined the correlation between energy dissipation and thermal responses by experimentally increasing the heel's collisional forces. Twenty healthy young adults walked overground on force plates and for 10 minutes on a treadmill (both at 1.25 ms-1) while wearing a vest with three different levels of added mass (+0%, +15%, & +30% of their body mass). We estimated the heel's work using a unified deformable segment analysis during overground walking. We measured the heel's temperature immediately before and after each treadmill trial. We hypothesized that the heel's temperature and net-negative work would increase when walking with added mass, and the temperature change is correlated with the increased net-negative work. We found that walking with +30% added mass significantly increased the heel's temperature change by 0.72±1.91 ℃ (p=0.009) and the magnitude of net-negative work by 326.94±379.92 J (p=0.005). However, we found no correlation between the heel's net-negative work and temperature changes (p=0.277). While this result refuted our second hypothesis, our findings likely demonstrate the heel's dynamic thermoregulatory capacity. If all the negative work were dissipated as heat, we would expect excessive skin temperature elevation during prolonged walking, which may cause skin complications (e.g., blisters, calluses, or ulcers in patients with vascular disease). Therefore, our results likely indicate that various heat dissipation mechanisms control the heel's thermodynamic responses, which may protect the health and integrity of the surrounding tissue. Also, our results indicate that additional mechanical factors, besides energy dissipation, explain the heel's temperature rise. Therefore, future experiments may explore alternative factors affecting thermodynamic responses, including mechanical (e.g., sound & shear-stress) and physiological mechanisms (e.g., sweating, local metabolic rate, & blood flow).